Journal of the Dead a story of friendship and murder in the New Mexico desert - Kersten, Jason (New York HarperCollins, 2003)
Traces the controversial 1999 case of best friends Raffi Kodikian and David Coughlin, who were found dead days after they became lost in the New Mexico desert along with evidence that Kodikian had murdered Coughlin
82352
Keywords: Kodikian, Raffi; Coughlin, David Andrew -- d. 1999; Homicide -- New Mexico -- Carlsbad Caverns National Park; Murder -- New Mexico -- Carlsbad Caverns National Park